The activity concentrations of 222Rn in some groundwater wells, Najran City, Saudi Arabia - Al-Naggar Tayseer I.; Abdalla Ayman M. (Nuclear Technology and Radiation Protection, 2017)
In this work, the radon exhalation rate, effective radium content and radiation doses from some groundwater wells in Najran City, Saudi Arabia, were addressed and discussed in detail. This survey of radon concentrations in the groundwater was carried out using the passive measurement technique, where the radon gas passively diffuses into the detector. The obtained results revealed that the radon exhalation rate in terms of area and mass exhibits linear correlations with effective radium in groundwater (correlation coefficient R2 = 1). Also, the majority of radon concentrations are within the UNSCEAR 1993 permitted level and the average annual effective doses obtained for radium and radon are 180 µSv and 860 µSv, respectively.